1980
DOI: 10.1152/jappl.1980.48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of centrifugation stress on pituitary-gonadal function in male rats

Abstract: The effects of centrifugation for various lengths of time were investigated on circulating levels of luteinizing hormone (LH) and testosterone in male rats. In a chronic 52-day experiment, centrifugation at 4.1 G significantly reduced LH and testosterone levels for the entire period. Centrifugation at 2.3 G had less effect inasmuch as LH levels were not significantly decreased and testosterone levels were significantly reduced only during the first few days of centrifugation. In more acute experiments, centrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
6
2
Order By: Relevance
“…Blood sampling at various time points during the periodic changes in plasma concentrations may mask the actual effects of microgravity and centrifugation. For example, in rats, plasma T was reduced over the first 4 days of centrifugation at 2.3 g (3); however, we have shown that excreted T was elevated over the first 8 days of centrifugation at 2 g (8). The use of 24‐hr urine excretion values is not biased by daily periodicity and may therefore provide a more accurate account of the effects induced by altered gravity on the pituitary‐gonadal axis.…”
contrasting
confidence: 53%
See 4 more Smart Citations
“…Blood sampling at various time points during the periodic changes in plasma concentrations may mask the actual effects of microgravity and centrifugation. For example, in rats, plasma T was reduced over the first 4 days of centrifugation at 2.3 g (3); however, we have shown that excreted T was elevated over the first 8 days of centrifugation at 2 g (8). The use of 24‐hr urine excretion values is not biased by daily periodicity and may therefore provide a more accurate account of the effects induced by altered gravity on the pituitary‐gonadal axis.…”
contrasting
confidence: 53%
“…Upon return to Earth, plasma LH was reported to be reduced on postspaceflight Day 8, whereas plasma T was elevated (4). During centrifugation at 2.3 g , plasma LH in rats was not significantly reduced, although plasma T was reduced on Days 1 and 4 with concentrations returning to control levels on Day 15 of exposure (3). Data from these studies suggest that a dissociation between plasma LH and T during exposure to altered gravity may exist.…”
mentioning
confidence: 68%
See 3 more Smart Citations